2008
DOI: 10.3748/wjg.14.2511
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory activity of probiotic Bifidobacterium: Enhancement of IL-10 production in peripheral blood mononuclear cells from ulcerative colitis patients and inhibition of IL-8 secretion in HT-29 cells

Abstract: AIM:To determine the anti-inflammatory activity of probiotic Bifidobacteria in Bifidobacteria-fermented milk (BFM) which is effective against active ulcerative colitis (UC) and exacerbations of UC, and to explore the immunoregulatory mechanisms. METHODS:Peripheral blood mononuclear cells (PBMNC) from UC patients or HT-29 cells were co-cultured with heat-killed probiotic bacteria or culture supernatant of Bifidobacterium breve strain Yakult (BbrY) or Bifidobacterium bifidum strain Yakult (BbiY) to estimate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
104
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(110 citation statements)
references
References 31 publications
5
104
0
1
Order By: Relevance
“…Moreover, both lactic acid and acetic acid were found to inhibit the production of pro-inflammatory cytokines, such as tumor necrosis factor-α and interleukin-8, from LPS-stimulated neutrophils and colon tumor cells. 22,29) However, quercetin had no such effect. Therefore, anti-inflammatory substance(s) produced by B. adolescentis during co-culture with the phytochemicals may be neither lactic acid nor acetic acid.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Moreover, both lactic acid and acetic acid were found to inhibit the production of pro-inflammatory cytokines, such as tumor necrosis factor-α and interleukin-8, from LPS-stimulated neutrophils and colon tumor cells. 22,29) However, quercetin had no such effect. Therefore, anti-inflammatory substance(s) produced by B. adolescentis during co-culture with the phytochemicals may be neither lactic acid nor acetic acid.…”
Section: Discussionmentioning
confidence: 81%
“…Phytochemicals, except for quercetin, increased the concentrations of lactic acid and acetic acid in the co-culture medium Since bifidobacterium bacteria is the major producer of lactic acid and acetic acid which were shown to have an anti-inflammatory activity, such as the inhibition of pro-inflammatory cytokine production, 22,29) we next investigated the change of pH and organic acids levels in the co-culture medium. After the culture of B. adolescentis with DMSO or phytochemicals [quercetin, (+)-taxifolin, phloretin, and EGCG] for 3 h, the pH of all of the tested supernatants decreased from 7.8 (just before culture) to 7.2 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, VSL#3 increased the basal luminal mucin content in rats by 60 % and significantly stimulated colonic mucin secretion and MUC2 gene expression in isolated rat colonic loops (62) . Finally, probiotics may affect the mucosal immune system by increasing the production of intestinal anti-inflammatory cytokines such as IL-10 and transforming growth factor β (63)(64)(65) , by modulating the NF-κB pathway (66) and by influencing the cross-talk between natural killer cells and dendritic cells (67) .…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%
“…Inflammation may reduce serum albumin level and severe hypo-albuminemia are common in critically ill patients [3]. Recently, it is suggested that consumption of probiotics would be a novel approach to decrease inflammation in humans [6,7]. Probiotics are kinds of living microorganisms which have beneficial health effects on humans.…”
Section: Introductionmentioning
confidence: 99%